(untitled) (Research, Society and Development, 2022)
The Intermunicipal Health Consortium of the West of Paraná (CISOP) was created to supply the low availability of specialized consultations caused by the lack of human resources to work in specialized centers. Thus, this work aims to analyze the functionality of specialized outpatient care of the 10th Health Regional, its integration with primary care and its main limitations. Methodology: The study comprised one physician from each area of ​​the main specialties of CISOP - psychiatry, orthopedics, endocrinology, cardiology, rheumatology, gynecology, general surgery, nephrology, neurology, pulmonology, urology, otolaryngology and pediatric surgeon. The choice of these specialties was due to the greater demand. All respondents answered a semi-structured questionnaire. Results: The results demonstrate that the waiting time for referral from primary health care to CISOP is 7.3 months, while the return time is 6.3 months. When questioning about the formation of the consortium, it is unanimous that the 10th regional contributed to strengthen the regional health system, 76.9% believe that the junction of municipalities provided scalability of care, as well as 92.3% believe in increased purchasing power. Therefore, most agree with the burden of responsibility, system slowness, in addition to accessibility issues and reference errors. Conclusion: the study showed that the CISOP emerges as a regional reinforcement tool for the expansion of the offer and specialized outpatient care, gain of scale in the provision of services. Although there are still challenges that demand a careful look.